Late Pleistocene-Holocene environmental change in eastern Turkey: multi-proxy palaeoecological data of vegetation and lake-catchment changes - Biltekin, Demet; Eris, Kursad Kadir; Cagatay, Memet Namik; On, Sena Akcer; Akkoca, Dicle Bal (Wiley, 2018)
This study presents the first pollen record from Lake Hazar, eastern Turkey, together with previously published multi-proxy records from core Hz11-P03. The data provide insight into multi-centennial-scale climatic changes during the late Pleistocene-Holocene period. The onset of the Younger Dryas was marked by an increase in the number of herbaceous plants (such as those in the families Poaceae and Asteraceae and the genus Centaurea) and lake level lowering with a -73m erosional terrace on the lake margin. At the beginning of the early Holocene, the expansion of deciduous Quercus was attributed to significant afforestation due to high humidity that was presumably sufficient for the establishment of the oak forest. An increase in deciduous Quercus was maintained until the middle Holocene. An increase in herbaceous plants, and lower lake levels occurred during the late Holocene as a result of cold and dry climatic conditions. Moreover, a deciduous Quercus delay was not detected in Lake Hazar, indicating that the presence of a warm and humid climate created favourable conditions for oaks to expand at the onset of the early Holocene.
Keywords: climate; Holocene; Lake Hazar; pollen; vegetation history